Proposal of a web information system to support cooperation networks: a functional architecture to share business opportunities - Mendonça, Vítor (2009)
The inter-organizational cooperation has established itself as a promising organizational model, enabling organizations to gain scale and simultaneously maintaining the flexibility necessary to constantly adapt to market demands ever-changing. This article, besides enhancing the strategic role of cooperation networks, intends to present the conceptual model and functional architecture of a Web Information System whose focus is the promotion of businesses networking. The proposed system will facilitate, based on the principles of cooperation networks, the establishment of cooperative arrangements between companies with complementary skills, allowing creating a web of companies oriented to customer loyalty within the networks, facilitating the sharing of information about customers and business opportunities.